2017
DOI: 10.22178/pos.25-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of Markov Model in Crude Oil Price Forecasting

Abstract: Abstract.Crude oil is an important energy commodity to mankind. Several causes have made crude oil prices to be volatile. The fluctuation of crude oil prices has affected many related sectors and stock market indices. Hence, forecasting the crude oil prices is essential to avoid the future prices of the non-renewable natural resources to rise. In this study, daily crude oil prices data was obtained from WTI dated 2 January to 29 May 2015. We used Markov Model (MM) approach in forecasting the crude oil prices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Statistical models, which are also known as random time series models, include exponential smoothing (ES) (see, e.g., Kourentzes et al [13]), auto-regressive integrated moving average (ARIMA) model (see, e.g., Guo [14]), generalized auto-regressive conditional heteroskedasticity (GARCH) model (see, e.g., Zhang et al [15]), hidden Markov model (HMM) (see, e.g., Isah & Bon [16]), and vectorial auto-regression (VAR) (see, e.g., Mirmirani & Li [17]). For example, Zolfaghari & Gholami [18] showed that ARIMA models had a good forecasting impact on international crude oil prices.…”
Section: Forecasting By Statistical Modelsmentioning
confidence: 99%
“…Statistical models, which are also known as random time series models, include exponential smoothing (ES) (see, e.g., Kourentzes et al [13]), auto-regressive integrated moving average (ARIMA) model (see, e.g., Guo [14]), generalized auto-regressive conditional heteroskedasticity (GARCH) model (see, e.g., Zhang et al [15]), hidden Markov model (HMM) (see, e.g., Isah & Bon [16]), and vectorial auto-regression (VAR) (see, e.g., Mirmirani & Li [17]). For example, Zolfaghari & Gholami [18] showed that ARIMA models had a good forecasting impact on international crude oil prices.…”
Section: Forecasting By Statistical Modelsmentioning
confidence: 99%
“…In addition, these models do not address the problem of dependency or correlation in data. The use of the hidden Markov models (HMMs) in forecasting the crude oil prices was adopted by several authors, for example, Bon and Isah (2016) and Isah and Bon (2017), who have both used, and also other researchers interested in using the HMMs in analyzing the oil prices, the frequentist principle in estimating and forecasting the model. Gong et al (2020) used a five-variable Markov switching vector autoregression (Markov switching VAR) taking into account the following variables: oil prices, oil aggregate demand, oil aggregate supply, global oil inventory and oil speculative demand.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these models do not address the problem of dependency or correlation in data. The use of the hidden Markov models (HMMs) in forecasting the crude oil prices was adopted by several authors, for example, Bon and Isah (2016) and Isah and Bon (2017), who have both used, and also other researchers interested in using the HMMs in analyzing the oil prices, the frequentist principle in estimating and forecasting the model. Gong et al .…”
Section: Introductionmentioning
confidence: 99%
“…Oil and gas play a momentous role in Malaysia, PETRONAS is the country's owned oil and gas company that contributed immensely to the economic development of Malaysia. PETRONAS contributed in the education sector of Malaysia; it also helped to the annual budget of Malaysia almost every year [4].…”
Section: Introductionmentioning
confidence: 99%